Marketing Communication Strategies in Building Brand Awareness: A Case Study of Sakinah Moeslim Bridal Pekanbaru - Tiara Venolia; Johan Faladhin; M Tazri (Journal of Communication, 2026)
The growth of the creative industry in Indonesia has encouraged the development of various local fashion brands. However, many local fashion businesses still face challenges in building strong brand awareness among consumers. Sakinah Moeslim Bridal & Boutique Pekanbaru is a local fashion brand that incorporates Malay cultural elements such as songket weaving, embroidery, and traditional motifs into its product designs. Despite having unique cultural characteristics, public recognition of the brand remains relatively limited. This study aims to analyze the marketing communication strategies implemented by Sakinah Moeslim Bridal & Boutique in building brand awareness of its local fashion products. The research uses a qualitative descriptive approach with the Integrated Marketing Communication (IMC) theory from Belch and Belch as the analytical framework. Data were collected through interviews, observation, and documentation involving two key informants from the company and four additional informants from the community. The results show that several marketing communication strategies are implemented to increase brand awareness. These include direct marketing through personal communication with consumers via WhatsApp, internet marketing through social media such as Instagram and websites, sales promotion through participation in regional and national fashion events or exhibitions, and publicity through media coverage. The integration of these strategies helps increase brand visibility and strengthen public recognition of the brand.